Customer's Decision-Making in Selecting Construction Contractors in Oudomxay Province - VONGPHACHANH, Anousack; VONGPHACHANH, Anousack (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The research objectives were to 1) determine the relative importance of contractor procurement factors, 2) examine the stages of the customer decision-making process, and 3) analyze the statistical correlation between these variables. A structured questionnaire was administered with 120 customers, selected using a convenience sampling method. Data were analyzed using SPSS version 25, employing descriptive statistics such as: frequency, percentage, mean, standard deviation, and inferential statistics through Pearson’s correlation coefficient. The findings indicate that 1) contractor procurement factors including experience, project management expertise, volume of work under responsibility, education of key personnel, and technical construction expertise were rated at a good level. 2) The customer decision-making process was rated from good to excellent, with “defining the problem” identified as the most critical stage. 3) Pearson correlation analysis showed a statistically significant high-level correlation (r = 0.611–0.800, p < 0.01) between contractor procurement factors and customer decision-making, confirming that improvements in contractor capability positively influence customer selection decisions. The use of a non-probability sampling method limits the generalizability of these results